Tal6 From Trichoderma atroviride Is a LysM Effector Involved in Mycoparasitism and Plant Association - Yordan J. Romero-Contreras; Claudia A. Ramírez-Valdespino; Paulina Guzmán-Guzmán; Juan Ignacio Macías-Segoviano; Julio César Villagómez-Castro; Vianey Olmedo-Monfil (Frontiers in Microbiology, 2019)
LysM effectors play a relevant role during the plant colonization by successful phytopathogenic fungi, since they enable them to avoid either the triggering of plant defense mechanisms or their attack effects. Tal6, a LysM protein from Trichoderma atroviride, is capable of binding to complex chitin. However, until now its biological function is not completely known, particularly its participation in plant–Trichoderma interactions. We obtained T. atroviride Tal6 null mutant and Tal6 overexpressing strains and determined the role played by this protein during Trichoderma-plant interaction and mycoparasitism. LysM effector Tal6 from T. atroviride protects the hyphae from chitinases by binding to chitin of the fungal cell wall, increases the fungus mycoparasitic capacity, and modulates the activation of the plant defense system. These results show that beneficial fungi also employ LysM effectors to improve their association with plants.